KEEFEKTIFAN BUKU AJAR BERBASIS LITERASI MATEMATIKA UNTUK MATERI “PERSAMAAN KUADRAT DAN FUNGSI KUADRAT” - Erlin Ladyawati; Sri Rahayu (JEDMA Jurnal Edukasi Matematika, 2022)
The purpose objective of this research is to determine the effectiveness of literacy-based textbook development on the material of Quadratic Equations and Quadratic Functions. The effectiveness of mathematical literacy-based textbooks for Quadratic Equations and Quadratic Functions material is determined from the value of classical learning completeness criteria and student response questionnaires that are positive. The development of this textbook uses the ADDIE model which stands for Analyze, Design, Development, Implementation, and Evaluation. From the data above, it is also obtained information that students 'responses to the use of mathematics literacy-based textbooks for Quadratic Equations and Quadratic Functions material for class IX Junior High School who answered "Yes" to all questions that were positive were 82.7%, meaning that the students' responses met positive criteria. Furthermore, in the learning result test or posttest, it can be seen that as many as 13 students completed their learning or got more than the KKM, which is 80, or if it is stated in percent, there are as many as 87% of students who are declared complete in their learning, this can be said that the class achieved classical completeness. From these results, it is found that the books that have been developed meet the effectiveness requirements.